Trends and challenges for the application of probiotic lactic acid bacteria in functional foods - Silva, Aline Sousa; Casarotti, Sabrina Neves; Penna, Ana Lúcia Barretto [UNESP] (FapUNIFESP (SciELO), 2024)
It is increasingly challenging for the food industries to develop products which meet the consumers’ demands. They seek foods that are innovative and present health benefits. In this review, the main objectives are to show the tendencies and innovations in the dairy food market and to indicate the challenges to apply probiotic bacteria to non-dairy products. Moreover, the safety of probiotic lactic acid bacteria (LAB) to be applied to food products and the beneficial effect of probiotic bacteria on the intestinal microbiota and overall human health were also discussed. We considered that the development of probiotic fermented products added with fruits and fruit by-products, cereals or other vegetables aligns with the market tendencies and the consumers’ demands.
Tendências e desafios para aplicação de bactérias láticas probióticas em alimentos funcionais
Keywords: fermentation; health; innovation; nutrition; vegetables